1990
DOI: 10.1111/j.1530-0277.1990.tb01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Taste Reactivity in Alcohol Preferring and Nonpreferring Rats

Abstract: Taste reactivity tests were used to examine the orofacial responses of alcohol preferring (P) rats and alcohol nonpreferring (NP) rats to the taste of alcohol. In the initial exposure, naive rats were tested for reactivity to five concentrations of alcohol (5%, 10%, 20%, 30%, and 40% v/v), water, and one solution each of sucrose and quinine. A two‐bottle consumption test was then given for a 3‐week period to allow the rats access to 10% alcohol. After the preference test, a second taste reactivity test was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 17 publications
4
39
0
1
Order By: Relevance
“…This is remarkable considering that even alcohol preferring (P) rats, which are genetically predisposed to consume very high levels of alcohol (Li et al 1979), show few hedonic responses to ethanol when alcohol-naive (Bice and Kiefer 1990;Kiefer 1995). Our observation that midazolam increases the hedonic response to ethanol also in alcohol-naive subjects may help to explain why druginduced increases in GABAergic transmission facilitate the acquisition of ethanol intake in rats (Smith et al 1992).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This is remarkable considering that even alcohol preferring (P) rats, which are genetically predisposed to consume very high levels of alcohol (Li et al 1979), show few hedonic responses to ethanol when alcohol-naive (Bice and Kiefer 1990;Kiefer 1995). Our observation that midazolam increases the hedonic response to ethanol also in alcohol-naive subjects may help to explain why druginduced increases in GABAergic transmission facilitate the acquisition of ethanol intake in rats (Smith et al 1992).…”
Section: Discussionmentioning
confidence: 60%
“…To control for the motor-impairing actions of the quite high doses of midazolam employed here, we also studied the e¤ect of the neuroleptic, cis(Z)ßu-pentixol, at a high cataleptic dose. Earlier studies relating ethanol preference to gustatory mechanisms include observations that rat lines high in alcohol consumption show unusually high levels of hedonic responses to the taste of alcohol (Bice and Kiefer 1990;Kiefer 1995), although Fahlke et al (1994) observed no correlation between home cage ethanol consumption and alcohol taste reactivity in our strain of unselected Wistar rats. Kiefer and Dopp (1989) reported that rats with access to alcohol in the home cage show fewer aversive responses to ethanol in the taste reactivity test compared to alcohol-naive subjects.…”
Section: Introductionmentioning
confidence: 48%
“…Instead of an effect on motivation for alcohol, STN lesions may have influenced the aversion mechanisms, as it has been shown that alcohol aversion is lower in alcohol preferring rats (tolerance to aversion) (Bice and Kiefer, 1990). As there was no difference between sham and STN rats on alcohol consumption, it is unlikely that STN lesions have induced a shift in alcohol-induced aversion tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…To equate for total volume and to account for dead space in the tubing, the syringe pump was set to an infusion rate of 1 ml/min and the pump remained activated for 1 min after an initial facial reaction (mouth movement) was observed by the experimenter (Bice & Kiefer, 1990). At the end of 1 min, the syringe pump was turned off, and facial reactions were recorded for one additional minute.…”
Section: Experiments 2: Palatability Testsmentioning
confidence: 99%